2012
DOI: 10.1517/14728222.2012.718330
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor coactivator-3 as a potential molecular target for cancer therapy

Abstract: Introduction Steroid receptor coactivator-3 (SRC-3), also called amplified-in-breast cancer-1 (AIB1), is an oncogenic coactivator in endocrine and non-endocrine cancers. Functional studies demonstrate SRC-3 promotes numerous aspects of cancer, through its capacity as a coactivator for nuclear hormone receptors and other transcription factors, and via its ability to control multiple growth pathways simultaneously. Targeting SRC-3 with specific inhibitors therefore holds future promise for clinical cancer therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 102 publications
1
29
0
Order By: Relevance
“…It is important to note that inhibition of SRC-3 is selectively toxic to cancer cells while sparing normal cells (16,17), and prior data showed that knockout of the SRC-3 gene does not influence adult mice life span (37). Consistent with our previously reported SRC-3 SMIs, we did not observe any toxicity of SI-2 up to 500 nM (the highest concentration used) in primary hepatocytes ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…It is important to note that inhibition of SRC-3 is selectively toxic to cancer cells while sparing normal cells (16,17), and prior data showed that knockout of the SRC-3 gene does not influence adult mice life span (37). Consistent with our previously reported SRC-3 SMIs, we did not observe any toxicity of SI-2 up to 500 nM (the highest concentration used) in primary hepatocytes ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Cyclin E, a cell cycle regulator, 31 and steroid receptor coactivator-3 (SRC-3), a transcriptional coactivator involved in inhibiting apoptotic responses, 32 were significantly increased in Mdm2 SNP309-G/G mice compared with Mdm2 SNP309-T/T mice following AOM treatment (Figure 5d, P = 0.0369 and P = 0.0228, respectively, and Supplementary Figure 4). Together these findings suggest that Mdm2 SNP309-G magnifies AOM-induced changes in ERα and Sp1 expression to alter ERα signaling and influence tumor phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…One previous research also demonstrated GA restrains the growth of xenografted GCB-and ABC-DLBCL cells in nude mice (Shi et al, 2015). In consideration of the therapy-resistant role of overexpressed SRC-3, inhibition of SRC-3 was also required in cancer chemotherapy especially for those chemoresistant cancers (Colo et al, 2007;Tien and Xu, 2012;Yi et al, 2013). GA could be used in combination with conventional chemotherapy to relieve the chemoresistance of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SRC-3 has been reported its regulation on histone acetylation through its AD1 domain by interacting with HATs or HDACs (Xu et al, 2009;Yan et al, 2006). And SRC-3 also contains HAT activity (Tien and Xu, 2012). …”
Section: Ga Did Not Affect the Akt Signaling Pathway But Induced Deacmentioning
confidence: 99%
See 1 more Smart Citation